Migration and seasonal distribution of Gadwall from Britain and Ireland: a preliminary assessment - Fox, A D; Mitchell, Carl (Wildfowl, 1988)
Analysis of 472 recoveries of Gadwall ringed in Britain and Ireland and of 36 foreign-ringed birds recovered in Britain and Ireland was carried out to determine the breeding origin of wintering birds and the wintering areas used by the summering population. Results are based on recoveries, where hunting accounts for 89% of known mortality. Between 33% and 50% of British wintering Gadwall derive from eastern Europe. Birds nesting in Iceland winter in Ireland and Scottish-breeding Gadwall also tend to move there to winter. Fifty-two percent of English-ringed pulli have been recovered in the Low Countries, France and Spain, which appear to represent the main wintering area for British-and Irish-ringed Gadwall recovered abroad. Overall, 46% of British-ringed Gadwall recoveries come from overseas, with males more likely to disperse across the Channel than females, and adults less likely to be recovered in Britain and Ireland than juveniles of either sex. The high proportion of males recovered in France and Spain in winter suggests abmigration may be involved.